ANALYSIS THE FISHING BUSINESS WITH TROLL LINE THAT MOORING AT MUARA PORT AREA SOUTH PADANG REGENCY PADANG CITY WEST SUMATERA PROVINCE - Fikri Irsyad Amami; Hendrik '; Darwis ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in January 2016 at Muara Port, South Padang Regency, Padang City, West Sumatera Province. This research purposed were to analyze how much the investation, gross income, nett income, the worthiness business from investation criteria RCR, FRR, and PPC, and also to know about the problem in the fishing business that used troll line ship with 5 GT and 6 GT size. This research used case study method with the determination respondent technique is purposive sampling, there are the owner of ship and fishing master. The research indicated that total investation from 5 GT troll line ship as Rp.300.386.902,50, gross income in every trip as Rp. 24.950.000, nett income in every trip as Rp. 11.195.805.00, RCR=1,29, FRR = 34 % , PPC = 54 trip. The total investation for 6 GT troll line ship as Rp.376.127.938,50, gross income in every trip as Rp.34.080.000,00, nett income in every trip as Rp. 17.076.677.00, RCR = 1,33, FRR = 41 %, PPC = 44 trip. The arrest business with 6 GT troll line ship is more profitable and worthy to continue than the 5 GT troll line ship. The problem are the difficult selling the fishing result, there’s no insurance for the worker, the difficult in administration process, decrease of fish quantity in the sea, and the high fuel price.Key Word : Troll Line, Investation, Income, Worthiness Business, Muara Port